2020
DOI: 10.1007/s40544-020-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

A synergetic strategy based on laser surface texturing and lubricating grease for improving the tribological and electrical properties of Ag coating under current-carrying friction

Abstract: Herein, a series of Ag coatings with different micro-dimples were fabricated on copper surfaces by laser surface texturing (LST) and magnetron sputtering. Multilayer graphene lubricating grease (MGLG) was prepared using multilayer graphene as an additive. The textured Ag coatings and MGLG were characterized. Moreover, the tribological and electrical performances of the textured Ag coatings under MGLG lubrication were investigated in detail. Results demonstrated that the textured Ag coating with an appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Since Guruswamy and Bockris first coined the term "Triboelectrochemistry" in 1980 [7], lubrication under EEFs has been vigorously developed based on the in-depth study of lubrication mechanisms and the urgent needs of industry [8][9][10]. Yoshitsugu et al [11] found that there is a threshold voltage for liquid crystal when used as a lubricant at the steel/steel interface under boundary lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Since Guruswamy and Bockris first coined the term "Triboelectrochemistry" in 1980 [7], lubrication under EEFs has been vigorously developed based on the in-depth study of lubrication mechanisms and the urgent needs of industry [8][9][10]. Yoshitsugu et al [11] found that there is a threshold voltage for liquid crystal when used as a lubricant at the steel/steel interface under boundary lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Different from this, sliding electrical contact not only needs to reduce the wear of contact interface, but also needs to pay attention to the conductivity or signal transmission ability between two relatively displaced parts. The wear resistance and conductivity of sliding electrical contact are important factors which affects the reliability and service life of sliding electrical contact [10][11][12]. Researchers have paid much attention to the conductivity and wear resistance of sliding contact parts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is widely used in various electrical contact occasions [20,21]. However, due to the accumulation of a large amount of heat in the electrical contact area, the soft Ag coating is very easy to form adhesive wear and abrasive wear, resulting in a sharp rise in contact resistance and wear [12,14]. Chromium nitride (CrN) coating is a multifunctional cermet coating with high hardness and melting point, excellent anti-wear and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, our attention is mainly focused on the electrical devices such as switch, parallel slot clamp and so on. When these electrical devices need to be lubricated, not only the lubricant is required to have good friction reducing and wear resistance properties, but also the lubricant should possess good electrical conductivity [19][20][21][22]. Although traditional lubricants have good lubricating properties, their conductivity is poor.…”
Section: Introductionmentioning
confidence: 99%